Methods for the Study of Marine Benthos. - Eleftheriou, Anastasios (Wiley, 2013)
The continuing global decline of the health of the sea, and the increasing depletion of marine resources and biodiversity, caused by human activity and climate change, have led to ever-increasing international concern. These changes in the marine environment highlight the importance of effective monitoring of the ecology of the benthos which has been shown to be a sensitive index of such alterations. Completely revised and updated to include many new methods and technologies, this Fourth Edition of Methods for the Study of Marine Benthos provides comprehensive coverage on the t.